1998
DOI: 10.1523/jneurosci.18-24-10672.1998
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action and Targets of Nitric Oxide in the Oculomotor System

Abstract: Nitric oxide (NO) production by neurons in the prepositus hypoglossi (PH) nucleus is necessary for the normal performance of eye movements in alert animals. In this study, the mechanism(s) of action of NO in the oculomotor system has been investigated. Spontaneous and vestibularly induced eye movements were recorded in alert cats before and after microinjections in the PH nucleus of drugs affecting the NO-cGMP pathway. The cellular sources and targets of NO were also studied by immunohistochemical detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Unilateral injections of NOS inhibitors within this nucleus produced velocity imbalances in a direction contralateral to the injected side, resulting in a dramatic and long-lasting nystagmus, which was more accentuated in darkness. Furthermore, local injections of NO donors produced a nystagmus in a direction opposite to that of NOS inhibitors, together with an alteration in eye position generation (Moreno-López et al, 1998). These functional data indicate that NO is tonically produced in the PH nucleus in normal conditions and suggest that NO acts by a retrograde action on nerve terminals from medial vestibular neurons projecting to the PH nucleus.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Unilateral injections of NOS inhibitors within this nucleus produced velocity imbalances in a direction contralateral to the injected side, resulting in a dramatic and long-lasting nystagmus, which was more accentuated in darkness. Furthermore, local injections of NO donors produced a nystagmus in a direction opposite to that of NOS inhibitors, together with an alteration in eye position generation (Moreno-López et al, 1998). These functional data indicate that NO is tonically produced in the PH nucleus in normal conditions and suggest that NO acts by a retrograde action on nerve terminals from medial vestibular neurons projecting to the PH nucleus.…”
mentioning
confidence: 71%
“…Functional experiments have identified neurons within this area that fire with eye position (McFarland and Fuchs, 1992), and therefore the primate marginal zone has been proposed as part of the integrator controlling eye movements (Kaneko, 1997). We have recently reported that this NO-responsive region may also have a role in the generation of the eye position after saccadic eye movements in the cat, based on the alterations in eye position observed when NO donors were injected in the proximity of these neurons (Moreno-López et al, 1998). However, the physiological significance of these results is not clear, because the marginal zone is devoid of nitrergic neurons, and the closest source of NO, the nitrergic PH neurons, is relatively distant for NO to reach the marginal zone cell bodies at adequate concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During spontaneous eye movements in darkness, the alterations induced by drug injections in the PH nucleus consisted of nystagmic eye movements with straight or curved slow phases separated by quick resetting eye movements. Linear and curved slow phases are indicative of two different alterations: velocity imbalance and eye-position generation failure, respectively (Cannon and Robinson, 1987;Godaux et al, 1993;Mettens et al, 1994a,b;Moreno-López et al, 1998). Slow phases with duration greater than 0.5 seconds were fitted separately, by the least-squares method, to linear and exponential equations, and were considered to be linear or exponential when more than 80% of the analyzed phases had a correlation coefficient Ͼ0.99 or Ͼ0.90, respectively.…”
Section: Physiological Experimentsmentioning
confidence: 99%
“…In neurons, NO targets mainly guanylyl cyclase, increasing cyclic guanosine monophosphate (cGMP), which in turn may exert a variety of effects via cGMP-dependent kinases and phosphodiesterases and cyclic nucleotide-gated ion channels (Lucas et al, 2000), depending on the neural type, cerebral region, and physiological state. In the PH nucleus, although there is a high number of nitrergic neurons, there are no nitroceptive neuronal bodies (Moreno-López et al, 1998, 2001, indicating that NO must be acting on the afferents that constitute part of the rich neuropil that is sensitive to NO within the nucleus. Retrograde tracer studies, in combination with immunocytochemistry using antibodies against cGMP and GABA, show that GABAergic terminals from the ipsilateral medial vestibular nucleus are targets for the NO released in the PH nucleus (MorenoLópez et al, 2001).…”
Section: No In Ph Neuronsmentioning
confidence: 99%